2010
DOI: 10.1167/iovs.09-4592
|View full text |Cite
|
Sign up to set email alerts
|

Variable Retinal Phenotypes Caused by Mutations in the X-Linked Photopigment Gene Array

Abstract: Novel and known mutations affecting the L-M opsin gene array were identified in families with X-linked cone-dominated phenotypes. The results show that different mutations in this gene array can cause a variety of phenotypes, including BCM, cone dystrophy, and maculopathy. Males with X-linked cone-dominated diseases should be routinely analyzed for mutations in the L-M opsin gene array.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 30 publications
1
58
0
Order By: Relevance
“…Consistent with the classical point of view has been the lack of detectable L-/M-cone function in three patients: one with a deletion genotype, and two patients with C203R missense mutations (Stockman et al, 1999). On the other hand, residual L-or M-cone function was found in a 23-year-old patient with the LIAVA type of mutation (Crognale et al, 2004), which is thought to cause abnormal splicing of exon 3 of the cone opsin gene (Ueyama et al, 2012), and in several young affected males in a family with a deletion genotype (Mizrahi-Meissonnier et al, 2010) very similar to the genotype of our Family 1. In patient P15, central vision was mediated by rods and S cones under darkadapted or standard ambient light conditions.…”
Section: Consequences Of Congenital Cone Opsin Deficiency On Conesmentioning
confidence: 88%
“…Consistent with the classical point of view has been the lack of detectable L-/M-cone function in three patients: one with a deletion genotype, and two patients with C203R missense mutations (Stockman et al, 1999). On the other hand, residual L-or M-cone function was found in a 23-year-old patient with the LIAVA type of mutation (Crognale et al, 2004), which is thought to cause abnormal splicing of exon 3 of the cone opsin gene (Ueyama et al, 2012), and in several young affected males in a family with a deletion genotype (Mizrahi-Meissonnier et al, 2010) very similar to the genotype of our Family 1. In patient P15, central vision was mediated by rods and S cones under darkadapted or standard ambient light conditions.…”
Section: Consequences Of Congenital Cone Opsin Deficiency On Conesmentioning
confidence: 88%
“…16 The remaining four subjects (JC_0347, JC_0564, JC_0118, KS_0577) had OPN1LW and OPN1MW mutations that fell into the newly discovered category involving intermixing of ancestral genes to produce L/M interchange mutations with deleterious combinations of nucleotides at normal polymorphic positions in exon 3. 7,8,10,13,19,24 All four of these subjects had a late-onset, progressive phenotype that was in stark contrast to that of the subjects with a C203R mutation or the To investigate the reduction in retinal thickness in more detail, we examined the thickness of the inner retina and the ONLþHFL from high-resolution horizontal cross sections (Fig. 1), and compared it to previously reported normative data.…”
Section: Different Genotype Classes Associated With Distinct Clinicalmentioning
confidence: 99%
“…These mutations can be placed into one of three categories: (1) mutations that produced random nonhomologous missense substitutions at single amino acid positions 1,3,12,16 ; (2) partial or complete deletion of an exon 15,23 ; and (3) a recently identified category involving intermixing of ancestral OPN1LW and OPN1MW genes to produce ''L/M interchange'' mutations with deleterious combinations of nucleotides at normal polymorphic positions. 7,8,10,13 While at least one L/M interchange mutation has been shown to directly cause cone malfunction (Greenwald SH, et al IOVS 2012;53:ARVO E-Abstract 4643), it was recently shown that in addition to any functional changes in the photopigment caused by the mutations, many of the L/M interchange mutations also interfere with recognition of exon 3 by the splicing mechanism. 24 Some of the variants incompletely interfere with splicing, so full-length mRNA is produced as well as the inappropriately spliced transcript.…”
mentioning
confidence: 99%
“…One deleterious variant has the amino acids leucine, isoleucine, alanine, valine, and alanine at amino acid positions 153, 171, 174, 178 and 180, respectively, and is abbreviated LIAVA. This variant has been associated with a color vision deficiency and blue cone monochromacy (Carroll et al , 2004; Crognale et al , 2004; Neitz et al , 2004; Mizrahi-Meissonnier et al , 2010). A second variant that differs from LIAVA only at position 171, where it has valine instead of isoleucine (LVAVA), has been associated with high myopia, cone dysfunction, and cone dystrophy (Carroll et al , 2012; McClements et al , 2013).…”
Section: Introductionmentioning
confidence: 99%